Optimizing water and nitrogen management in a wheat–maize rotation system: synergistic increases in grain yield, resource use efficiency, and economic and environmental benefits - Kong, Weilin; Gao, Chunhua; Zhao, Fengtao; Ju, Feiyan; Li, Zongxin; Zhao, Haijun; Liu, Kaichang; Liu, Ping (Frontiers in Plant Science, 2026)
IntroductionOptimizing water and nitrogen management is crucial for the sustainable development of wheat–maize rotation system. This study systematically examined the impacts of various water and nitrogen management strategies on the wheat–maize rotation system, with the aim of identifying integrated practices that can simultaneously improve yield, resource use efficiency, economic returns, and environmental outcomes.MethodsA field experiment was conducted from 2022 to 2024 in Tai’an, Shandong Province, China. Strategies involved different nitrogen fertilizers (compound fertilizer, urea, and controlled-release fertilizer) and irrigation methods (flood, drip irrigation DI, and micro-sprinkler irrigation SI). Outcomes were assessed based on yield, water and nitrogen use efficiency, economic benefits, and environmental performance, using entropy-weighted TOPSIS comprehensive evaluation. This research aiming to identify an optimized management practice that can simultaneously. enhance both economic and carbon benefits(carbon sequestration/emission ratio).Results and discussionDrip irrigation with 60% basal controlled-release fertilizer and 40% top-dressed urea (T4) yielded optimal results. Compared to conventional flood irrigation with 50% basal compound fertilizer and 50% top-dressed urea, T4 synergistically increased annual system yield by 1.08–3.99%, improved water use efficiency to 9.42 kg·m-3 and nitrogen use efficiency to 34.75%, achieved the highest net income (24,347.9 CNY·ha-1), and raised carbon benefits to 21.38. Entropy-weighted TOPSIS comprehensive evaluation further demonstrated that the T4 treatment under drip irrigation obtained the highest closeness coefficient (0.702). These findings show that integrating drip irrigation with the split application of controlled-release fertilizer and urea can facilitate the efficient alignment of water and nitrogen resources. This approach is a viable technical pathway for promoting sustainable and low-carbon production under the wheat–maize rotation system in the Huang–Huai–Hai region of China.